MODELLING INTELLIGENT MULTI-MODAL TRANSIT SYSTEMS - Nuzzolo, Agostino, editor; Lam, William H. K., editor (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2017)
Includes bibliographical references and index.